Contemporary Strategies in the Management of Civilian Neck Zone II Vascular Trauma - Karaolanis, Georgios; Maltezos, Konstantinos; Bakoyiannis, Chris; Georgopoulos, Sotiris (Frontiers in Surgery, 2017)
Neck trauma is the leading cause of death mainly in younger persons posing to surgeons the dilemma whether to proceed with reconstruction of vascular injuries either in the presence of coma or in severe neurological deficit. Vascular injuries in zone II predominate over the other injuries located in zones I/III of the neck. Conventional open repair of carotid injuries with primary closure or interposition grafting is always recommended due to the effective long-term results for penetrating injuries or for patients unfit for endovascular intervention. In cases of blunt trauma, anticoagulation or antiplatelet therapy should be administered first in neurologically stable patients. In case of worsening of the neurological status of the patient despite adequate anticoagulation endovascular means should be considered in cases of appropriate anatomy of the arterial trauma. We provide an update on penetrating/blunt trauma in zone II of the neck, giving emphasis on the anticoagulant and endovascular treatment.